A change in social participation affects cognitive function in middle-aged and older Chinese adults: analysis of a Chinese longitudinal study on aging (2011–2018) - Li, Xuyang; Xu, Wenyan (Frontiers in Public Health, 2024)
One of the biggest challenges facing the elderly is cognitive decline, social participation has always been considered a protective factor. However, it was not clear whether social participation predicted cognitive function in the sample, rather than depressive symptoms, self-reported health and activities of daily life, with sufficient capacity to detect unique effects. This study included adults aged 45 and above in China (N = 5258) who participated in a large national elderly health survey and provided data from 2011, 2013, 2015, and 2018. The unique associations between the predictors of social participation and cognitive function over time and context were evaluated in the Latent Growth Model (LGM). Among 5258 participants for our study, there is an overall cognitive decline. Social participation predicts two dimensions of cognitive function, with a degree of impact comparable to depressive symptoms, self-reported health and activities of daily life. Among them, social participation exhibits a noteworthy prognostic impact on episodic memory during the same period. The regression coefficient is around 0.1(p<0.05) and after controlling other mixed variables (depressive symptoms, self-reported health and activities of daily life). In contrast, social participation is also a significant predictor of mental intactness in the same period, with a regression coefficient of 0.06 (p<0.05), even if all mixed variables are controlled. Over time, the correlation strength of social participation is comparable to other recognized cognitive function prediction indicators, indicating that promoting social participation among middle-aged and older Chinese as a meaningful way to improve cognitive function degradation, which has important policy and practical significance.